The Importance of Mastering the Pedagogical Sources of the New Ideology - Akram Yuldashevich Utayev (Academia One Publishing, 2023)
the article reflects on the importance of mastering the pedagogical resources of the Vangi ideology, in which the main pedagogical and political resources and the ideas of the new ideology in our pedagogical heritage are interpreted.
Keywords: ideology; pedagogy; politics; source